Electrocatalytic activity of Ti3SiC2/TiC composite materials in hydrogen evolution reaction in 0,5 mol/l H2SO4 solution - Firsova Ольга Александровна; Panteleeva Виктория Вячеславовна (Bulletin of Perm University. CHEMISTRY, 2023)
The electrochemical activity of Ti3SiC2/TiC composite materials obtained by spark plasma sintering of a mechanoactivated mixture of 3Ti/1,25SiC/0,75C in 0,5 M H2SO4 solution has been studied. It is shown that the cathode potentiostatic curves of Ti3SiC2/TiC electrodes have the same type and are characterized by the presence of Tafel section with constants a and b equal to -(0,44–0,62) and -(0,060–0,075) V, respectively. An increase in the content of the Ti3SiC2 phase in the composition of the composite material leads to an increase in the rate of the hydrogen release reaction. It is concluded that Ti3SiC2/TiC composite materials in sulfuric acid electrolyte are promising for the electrolytic production of hydrogen.